SARS-CoV-2 N protein promotes NLRP3 inflammasome activation to induce hyperinflammation - Pan, Pan; Shen, Miaomiao; Yu, Zhenyang; Ge, Weiwei; Chen, Keli; Tian, Mingfu; Xiao, Feng; Wang, Zhenwei; Wang, Jun; Jia, Yaling; Wang, Wenbiao; Wan, Pin; et al. (Nature communications, 2021)
Excessive inflammatory responses induced upon SARS-CoV-2 infection are associated with severe symptoms of COVID-19. Inflammasomes activated in response to SARS-CoV-2 infection are also associated with COVID-19 severity. Here, we show a distinct mechanism by which SARS-CoV-2 N protein promotes NLRP3 inflammasome activation to induce hyperinflammation. N protein facilitates maturation of proinflammatory cytokines and induces proinflammatory responses in cultured cells and mice. Mechanistically, N protein interacts directly with NLRP3 protein, promotes the binding of NLRP3 with ASC, and facilitates NLRP3 inflammasome assembly. More importantly, N protein aggravates lung injury, accelerates death in sepsis and acute inflammation mouse models, and promotes IL-1β and IL-6 activation in mice. Notably, N-induced lung injury and cytokine production are blocked by MCC950 (a specific inhibitor of NLRP3) and Ac-YVAD-cmk (an inhibitor of caspase-1). Therefore, this study reveals a distinct mechanism by which SARS-CoV-2 N protein promotes NLRP3 inflammasome activation and induces excessive inflammatory responses. SARS-CoV-2 infection has been shown to drive NLRP3 inflammasome activation and thereby cytokine storm, but how it does so is unclear. Here the authors show that the viral N protein can bind to NLRP3, resulting in enhanced interaction with ASC and thereby with the NLRP3 inflammasome.